Promoting Religious Moderation in Social Media (A Study on the Qur’anic Exegesis of Q.S. al-Kafirun by Habib Husein Ja’far on “Habib and Cing” Youtube Channel) - Zaenal Muttaqin; Azka Zahro Nafiza (2022)
This article discusses the promotion of religious moderation and tolerance in social media. The study focuses specifically on how Habib Husein Ja’far interprets the Qur’an on “Habib dan Cing” YouTube channel, particularly on Q.S. al-Kafirun (109). Social media nowadays are considered the effective and relevant means of communication so that modern preachers actively engage in the various platforms of social media to deliver Islamic messages. Habib Husein and Abdel Achrian, among others, employ YouTube channel called “Habib dan Cing” to perform da’wa which contains the interpretation of the Qur’anic verses (tafsir). This paper focuses specifically on the interpretation of the Qur’an sura al-Kafirun (The Disbelievers) by Habib Husein broadcasted in the channel. This research finds that Habib Husein’s Qur’anic interpretation of sura al-Kafirun attempt to persuade people to be moderate and tolerance to others. Among Habib Husein’s moderation are his explanation of the term kafir which is not understood merely disbelievers or non-Muslims, but also for those who have bad attitudes by referring to qualities such as ungrateful, unfaithful, liar, and obstinate. Commenting on the last verse, Habib Husein also explains that din can be understood as reward, meaning that people are only responsible and rewarded for they have done, not for others have done. Therefore, no need to be angry for those who trespass or force them to uphold Islamic teachings. Using virtual ethnography analysis, Habib Husein’s interpretation of the Qur’an is easily understood since he explains in a relax style and inserts popular jokes. Yet, Habib Husein still refers to classical tafsir which indicates his broad and deep knowledge of Islamic sciences while also connects his tafsir to the contemporary social context of Indonesia.